Soccer and Benign Paroxysmal Positional Vertigo - Warming, Nikolaj; Andersen, Stephanie Balslev; Hougaard, Dan Dupont (Case Reports in Otolaryngology, 2023)
Introduction. Benign paroxysmal positional vertigo (BPPV) is the most common cause of vertigo among adults. The etiology of BPPV is unknown in approximately 50 percent of cases. This condition is also termed primary BPPV, if the etiology is unknown, and secondary BPPV if patients have identified predisposing factors. A few studies suggest that there is a correlation between the development of BPPV and specific sports. Case Report. A 19-year-old male presented with recurrent episodes of vertigo during soccer play. Eight months prior to referral, the patient was involved in a car accident with a mild head trauma. The patient was later diagnosed with BPPV several times. Discussion. Soccer might be a plausible BPPV trigger, especially if there is a prehistory of head trauma. This is most likely due to the demands of the game such as the change of directions, repetitive head impacts (headers or head collisions), accelerations/decelerations, jumps, foot landings, and rapid head movements.